Last of the green: identifying priority sites to prevent plant extinctions in Brazil. Issue 1 (2nd February 2016) - Diniz, Milena F.; Gonçalves, Tatiel V.; Brito, Daniel
Abstract: The identification and protection of Alliance for Zero Extinction sites at the national level is of great importance to safeguard biodiversity and achieve the targets of the Convention on Biological Diversity for 2020. Here we identify priority species and sites for the Brazilian flora. We evaluated the protection status of each site, taking into account whether or not it was located within a protected area, and the anthropogenic pressure on the site, using human density and gross domestic product as surrogates. We identified a total of 234 trigger species at 140 sites. Most of the sites are located in the Atlantic Forest and the Cerrado; only 21 are within protected areas. There was no relationship of human density and annual gross domestic product per capita with the level of site protection. The low proportion of Alliance for Zero Extinction sites protected shows that Brazil is lagging behind in global conservation efforts to protect such sites.